The Influence of Product Diversity, Experiential Marketing and Service Quality on Customer Satisfaction - Dimas Oktorio Fadilla; Nurhadi Nurhadi (International Journal of Economics Development Research (IJEDR), 2024)
This study was conducted to determine the effect of product diversity, experiential marketing, and service quality on consumer satisfaction of coffee shops in Bojonegoro. The type of research used is quantitative research. The population in this study is coffee connoisseurs located in Bojonegoro Regency. This study used a sample of 151 respondents using non-probability sampling methods and sampling techniques, namely purposive sampling. Multiple linear regression analysis was applied to analyze data tested with SPSS version 25. This research states that simultaneously product diversity, experiential marketing, and service quality affect consumer satisfaction. Partially, product diversity, experiential marketing, and service quality have a significant effect on consumer satisfaction.